2011
DOI: 10.1063/1.3585148
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of solvent evaporation from polymer jets in electrospinning

Abstract: Solvent evaporation plays a critical role in nanofiber formation in electrospinning. Here, we present a nonlinear mass diffusion-transfer model describing the drying process in dilute polymer solution jets. The model is used to predict transient solvent concentration profiles in polyacrylonitrile/N,N-dimethylformamide (PAN/DMF) jets with the initial radii ranging from 50 μm down to 100 nm. Numerical simulations demonstrate high transient inhomogeneity of solvent concentration over the jet cross-section in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 30 publications
1
55
0
2
Order By: Relevance
“…This would be consistent with the presence of a slowly evaporating solvent component, i.e. with a jet time-of-flight which is comparable with the drying time scale, 35,37 and supported by the joints observed in SEM micrographs of intersecting deposited fibers (e.g., Figure 1b,c).…”
Section: Resultssupporting
confidence: 80%
“…This would be consistent with the presence of a slowly evaporating solvent component, i.e. with a jet time-of-flight which is comparable with the drying time scale, 35,37 and supported by the joints observed in SEM micrographs of intersecting deposited fibers (e.g., Figure 1b,c).…”
Section: Resultssupporting
confidence: 80%
“…Variability in mechanical properties of fibers within a single synthetic batch may be due to inherent sample heterogeneity introduced by the stochastic electrospinning process (34). Studies have shown that electrospun fibers dry very rapidly as they are drawn through a spatially varying electric field (35), causing them to experience heterogeneous tensile forces and develop highly varying structures (36). The error bar in the Young's modulus also increased with concentration, likely due to nanoparticle aggregates increasing the heterogeneity of the nanocomposite morphology and acting as nucleation sites for defects.…”
mentioning
confidence: 99%
“…Electrospinning is a promising technique to manufacture superfine fibers and has attracted a great deal of attentions in recent decade. [1][2][3][4][5][6][7][8][9][10][11][12] In this procedure, the polymer solution is pumped through a syringe needle, and subsequently, is ejected to form a thin jet under the action of electrostatic force imposed by a high-voltage electric field, then the stretched polymer fibers dissolved in the spinning solution are deposited on the collector after the solvent evaporates almost completely. Thus, controlling the morphology of fibers in spinning solution and adjusting the evaporation rate are especially important for preparing the high-quality fiber.…”
mentioning
confidence: 99%